Synergic Use of Multi-Sensor Satellite Data for Volcanic Hazards Monitoring: The Fogo (Cape Verde) 2014–2015 Effusive Eruption - Bignami, Christian; Chini, Marco; Amici, Stefania; Trasatti, Elisa (Frontiers in Earth Science, 2020)
Monitoring and retrieving information of volcanic eruptions are important tasks for assessing the hazard and its evolution in time. Satellite remote sensing data are nowadays suitable tools to perform such tasks, thanks to their capability to access disastrous event also in remote and under-monitored regions, with frequent revisit time and accurate spatial information. In this work, we have analyzed satellite images, coming from both Synthetic Aperture Radar (SAR) and Optical sensors, to characterize the 2014-2015 eruption of Fogo volcano, Cape Verde. In particular, we have exploited images collected by the European Space Agency (ESA) Sentinel-1, the Italian Space Agency (ASI) COSMO-SkyMed, and NASA/USGS Landsat-8 and Earth-Observing-1 missions, for studying the lava emplacement and volcanic source of the eruption that took place between November 2014 and January 2015. On one side, we have adopted a new automatic change detection technique for estimating the lava field and its temporal evolution, taking advantage of the intensity and the Interferometric SAR coherence. The two SAR-based features were combined using an innovative algorithm able to take full advantage of the Sentinel-1 mission’s six-day repeat cycle, thereby providing an unprecedented possibility to fully exploit the multi-temporal InSAR coherence to detect surface changes. On the other side, we have exploited the consolidated differential SAR interferometry technique to map the ground deformation and retrieve the feeding dyke by inverting syn-eruptive data. The proposed methods based on change detection for the estimation of the lava flow is capable of resolving with spatial and temporal detail the evolution of lava flows. Results from source modelling from the SAR data show a SW-NE oriented dyke, located inside Chã das Caldeiras, SW of the Pico do Fogo. The work suggests a multidisciplinary and multi-sensor approach, highlighting the benefits and limitations of satellite data and image processing techniques in an operational environment.